2019
DOI: 10.1186/s12889-019-8005-5
|View full text |Cite
|
Sign up to set email alerts
|

Living in the shadow of unemployment -an unhealthy life situation: a qualitative study of young people from leaving school until early adult life

Abstract: BackgroundDespite the magnitude of youth unemployment there is a lack of studies, which explore the relations between health experiences and labour market position in various contexts. The aim of this paper was to analyse health experiences among young people in NEET (not in education, employment or training) in relation to labour market position from leaving school until early adult life.MethodThe population consists of everyone (six women, eight men) who became unemployed directly after leaving compulsory sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
(45 reference statements)
1
13
0
1
Order By: Relevance
“…[48][49][50][51][52] Such interventions may be particularly salient for NEET youth, who have been reported as highly vulnerable to stress as a result of their NEET status. 27,53 Our results also showed that young adults generally fear embarking on lifelong medication use. This is consistent with other research and suggests that medication adherence in young adults is generally low, 18,54,55 and medication side-effects are the main barrier to adherence in young adults with HTN.…”
Section: Pt 6 -F; Neet Group: "I Would Honestly Ignore You (If You To...supporting
confidence: 63%
See 1 more Smart Citation
“…[48][49][50][51][52] Such interventions may be particularly salient for NEET youth, who have been reported as highly vulnerable to stress as a result of their NEET status. 27,53 Our results also showed that young adults generally fear embarking on lifelong medication use. This is consistent with other research and suggests that medication adherence in young adults is generally low, 18,54,55 and medication side-effects are the main barrier to adherence in young adults with HTN.…”
Section: Pt 6 -F; Neet Group: "I Would Honestly Ignore You (If You To...supporting
confidence: 63%
“…4852 Such interventions may be particularly salient for NEET youth, who have been reported as highly vulnerable to stress as a result of their NEET status. 27,53…”
Section: Discussionmentioning
confidence: 99%
“…Disengagement from school and work may further disadvantage those with mental health problems, widening the gap between them and peers who follow more engaged developmental trajectories. Disengagement may also further heighten feelings of shame, hopelessness, and social exclusion [ 20 , 51 ]. Analyses for NEET status predicting the later occurrence of mental health problems aggregated, substance use problems aggregated, and all measures combined were not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantaged situation of NEET youth is further exacerbated by health problems (OECD 2015b;Hammarström and Ahlgren 2019;Stea et al 2019) and gender (Russell 2016 a,b;Saczyńska-Sokół 2018). Therefore, NEET youth require a complex, multi-faceted approach since gender, place of residence, manner of intervention, possible financial support, disability, and other temporal factors can all significantly impact upon whether young people are in employment or education (Luthra et al 2018).…”
Section: Reasons and Solutions For Neet Statusmentioning
confidence: 99%